CREATIVE INDUSTRY DEVELOPMENT IN PESANTREN TEBUIRENG - Al Hasyim, M. Musa (IAIN Surakarta, 2019)
Film, short movie, and animation are one of the sub-sectors in creative industry which are importantly considered for development of Indonesia?s creative economy. Pesantren (Islamic boarding school) have opportunity to get involve it. Kopi Ireng (Komunitas Photography Tebuireng, Tebuireng Photography Community) inspired Tebuireng santri to establish production house, namely Maksi (Rumah Produksi Tebuireng, Tebuireng Production House). Kopi Ireng has won many competitions while Maksi has produced two movies both Binar and Sakinah. Both Kopi Ireng and Maksi are an effort to regenerate the progress of film industry in Indonesia, especially in pesantren. Film in pesantren is something new which is sometimes considered unusually. Some of pesantren claimed that film activity will break the old tradition of santri and pesantren in studying Islamic studies. Both Kopi Ireng and Maksi believe that film is the way to spread dakwah and origin culture of Indonesia in the era of 4.0 industrial revolution. Keyword: 4.0 era, creative industry, film, Pesantren Tebuireng